1995
DOI: 10.1073/pnas.92.17.8016
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of autocrine modulation of macrophage nitric oxide synthase by alpha-melanocyte-stimulating hormone.

Abstract: a-Melanocyte-stimulating hormone (a-MSH) is a potent inhibitory agent in all major forms of inflammation. To identify a potential mechanism of antiinflammatory action of a-MSH, we tested its effects on production of nitric oxide (NO), believed to be a mediator common to all forms of inflammation. We measured NO and a-MSH production in RAW 264.7 cultured murine macrophages stimulated with bacterial lipopolysaccharide and interferon Y.a-MSH inhibited production of NO, as estimated from nitrite production and nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
251
0
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(268 citation statements)
references
References 49 publications
15
251
0
2
Order By: Relevance
“…One consequence of this could be that MC1R also could be expressed on haematopoietic cells. Indeed, stimulated monocytes and macrophage lines were shown to express MC1R (Star et al, 1995;Bhardwaj et al, 1997). Our data indicated that while MC1R is not expressed at detectable levels on fresh monocytes, in vitro stimulation with several cytokines such as IL-4, GM-CSF, and IL-10 can induce a strong expression of this receptor (Figures 4 and 5A,B).…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…One consequence of this could be that MC1R also could be expressed on haematopoietic cells. Indeed, stimulated monocytes and macrophage lines were shown to express MC1R (Star et al, 1995;Bhardwaj et al, 1997). Our data indicated that while MC1R is not expressed at detectable levels on fresh monocytes, in vitro stimulation with several cytokines such as IL-4, GM-CSF, and IL-10 can induce a strong expression of this receptor (Figures 4 and 5A,B).…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%
“…Alpha-melanocyte stimulating hormone (a-MSH) is a tridecapeptide derived from the precursor molecule propiomelanocortin (POMC) (Eberle, 1988) and is primarily released by the pituitary, but also by immunocompetent cells (Schauer et al, 1994;Farooqui et al, 1995;Star et al, 1995). a-MSH is a very potent stimulator of the pigmentation and differentiation of pigmented cells, including melanoma cells (Schwahn et al, 2001).…”
mentioning
confidence: 99%
“…In mammals, there have been several studies investigating a possible role of MC1R in the immune system. MC1R is expressed in many leucocytes (Catania et al 1996;Neumann et al 2001) and the melanocortin peptide a-MSH, which is an MC1R agonist, has well-established anti-inflammatory effects (Star et al 1995). However, no evidence of immune dysfunction has been reported in mice or humans which lack functional MC1R.…”
Section: Why Mc1r?mentioning
confidence: 99%
“…To test the idea that the primary ␣-MSH receptor MC-1, recently found in murine macrophages and in human macrophages and neutrophils (Star et al, 1995;Rajora et al, 1996;Catania et al, 1996), likewise occurs in brain tissue, normal mouse brain was subjected to RT-PCR and Southern analysis. This analysis revealed a substantial signal at 529 bp, consistent with the size of the cDNA for the murine MC-1 receptor (Fig.…”
Section: Evidence Of Mc-1 Receptor Expression In the Brainmentioning
confidence: 99%